2020
DOI: 10.1051/e3sconf/202022203002
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of dill freeze-drying technology

Abstract: In this work, we studied the use of IR pretreatments before freeze drying of dill. The indicators of the drying period, the process of rehydration of different samples dried by the sublimation method with and without pretreatment are compared. Experimentally, data have been obtained that when using IR pretreatment, the drying process is reduced by about 4-5 hours. The main reasons for the shortening of the freeze drying period is to reduce the moisture content to 25-30% during pre-treatment. The data confirms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…In [23][24][25][26][27] the results of phosphate fertilizer process investigation using decompose of phosphorite with mixture of phosphoric and sulphuric acids at ratios of SO3: Р2О5 equal to 1.2; 1.65; 2.6, as well as at various ratios of acids mix to phosphate raw materials, have been given. The advantages of this process in comparison with ammonium sulphate-phosphate were shown.…”
Section: Introductionmentioning
confidence: 99%
“…In [23][24][25][26][27] the results of phosphate fertilizer process investigation using decompose of phosphorite with mixture of phosphoric and sulphuric acids at ratios of SO3: Р2О5 equal to 1.2; 1.65; 2.6, as well as at various ratios of acids mix to phosphate raw materials, have been given. The advantages of this process in comparison with ammonium sulphate-phosphate were shown.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, only various incandescent lamps with a heating temperature of 2000 -3000°C can be used as such illuminators. Scientific papers [3] present theoretical and experimental results of the study of the mechanism of light energy transfer. It is shown that the high-frequency part of the radiation spectrum has the most polarizing effect on dielectric materials.…”
Section: Introductionmentioning
confidence: 99%